A phase 2b, randomized, placebo-controlled, double-blind, dose-ranging study of the neurokinin 3 receptor antagonist fezolinetant for vasomotor symptoms associated with menopause. Issue 4 (April 2020) - Fraser, Graeme L.; Lederman, Samuel; Waldbaum, Arthur; Kroll, Robin; Santoro, Nanette; Lee, Misun; Skillern, Laurence; Ramael, Steven
Abstract: Objective: Menopausal vasomotor symptoms (VMS) may result from altered thermoregulatory control in brain regions innervated by neurokinin 3 receptor-expressing neurons. This phase 2b study evaluated seven dosing regimens of fezolinetant, a selective neurokinin 3 receptor antagonist, as a nonhormone approach for the treatment of VMS. Methods: Menopausal women aged >40-65 years with moderate/severe VMS (≥50 episodes/wk) were randomized (double-blind) to fezolinetant 15, 30, 60, 90 mg BID or 30, 60, 120 mg QD, or placebo for 12 weeks. Primary outcomes were reduction in moderate/severe VMS frequency and severity ([number of moderate VMS × 2] + [number of severe VMS × 3]/total daily moderate/severe VMS) at weeks 4 and 12. Response (≥50% reduction in moderate/severe VMS frequency) was a key secondary outcome. Results: Of 352 treated participants, 287 completed the study. Fezolinetant reduced moderate/severe VMS frequency by −1.9 to −3.5/day at week 4 and −1.8 to −2.6/day at week 12 (all P < 0.05 vs placebo). Mean difference from placebo in VMS severity score was −0.4 to −1 at week 4 (all doses P < 0.05) and −0.2 to −0.6 at week 12 ( P < 0.05 for 60 and 90 mg BID and 60 mg QD). Response (50% reduction) relative to placebo was achieved by 81.4% to 94.7% versus 58.5% of participants at end of treatment (all doses P < 0.05). Treatment-emergent adverse events were largely mild/moderate; no serious treatment-related treatment-emergent adverse events occurred. Conclusions: Fezolinetant is a well-tolerated, effective nonhormone therapy that rapidly reduces moderate/severe menopausal VMS. N/A: Video Summary: http://links.lww.com/MENO/A572 ; video script available at http://links.lww.com/MENO/A573 . Abstract : Supplemental Digital Content is available in the text